Atención farmacéutica en establecimiento privado Inkafarma Trujillo 40 durante el periodo enero 2015 – enero 2016 - Quezada Jara, Mario Miguel (2016)
This report was made in order to publicize the Pre Professional Practices conducted from January 2015 to January 2016 in the Pharmaceutical Establishment Inkafarma Eckerd Peru SA, Local TRUJILLO 40 located in the city of Trujillo, Trujillo district, province Trujillo, La Libertad department, under the guidance of technical director of the local, pharmaceutics Karen Priscila Barrantes Rojas. In this report the various functions performed during pre-professional practices and activities to improve pharmaceutical care, which generally are focused on, dispensing medicines, pharmaceutical indication custody of substances under legal control are described, and development of expository lectures personnel among other activities, mentioning the objectives of each and how they performed, indicating briefly what is the role of the Pharmaceutical Chemist in such activities and the work performed collaborator staff within them, all important for the functioning of the local being some of them governed by laws and government regulations in our country, plus analysis was performed to improve pharmaceutical care in order to provide quality care to the public